CARTOON STORY MAKER AS THE DEVELOPED LEARNING MEDIA IN WRITING DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL STUDENTS - Bahagia Saragih (BAHAS, 2019)
Abstract  The aim of this study was to develop learning media in Writing Descriptive Text. This study was conducted at junior high school level students by applying six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product.. The data were gathered  by administering interview to English teacher and distributing questionnaire to 30 respondents to get the students’ needs. The interview and questionnaire results prove that the students needs English learning media which can motivate the students to understand about the descriptive writing. The product has been validated by experts. The result of the product was videos that contain audio-visual media to be used in mastering the descriptive text writing. Keywords: Cartoon Story Maker,Learning Media, Descriptive Text